Reassessment of Widal test in the diagnosis of Typhoid Fever - Mussa, Ali (Diyala Journal of Medicine, 2019)
This study was done on 3 group of population. Group 1 comprised 80 normal, healthy, non febrile individuals with a negative history for typhoid fever and no history of immunization against typhoid fever . Group 2 comprised 50 patient with a febrile illness rather than typhoid fever with also no history of typhoid fever and no history of immunization against typhoid fever. Group 3 comprised 18 patient with bacteriologically confirmed typhoid fever and by using a new statistical approach for the calculation of the cut off value for categorizing positive and negative Widal test, the cut off value for O titer was 1/104 and for H titer was 1/120 The result of this study in group 1 showed that the Widal test was positive in 38,7% for O titer and 40% for H titer, and the number of cases with a titer 1/320 was 7 cases for O titer and 11 cases for H titer . the result in group 2 showed that the Widal test was positive in 20 cases for O titer and from these cases . 7 cases with a titer of 1/320. While positive test for H titer was 23 cases and from these, 11 cases with a titer 1/320 . In group 3 the Widal test was positive in all cases for both O & H titers and the number of cases with a titer 1/320 was 15 cases for O and 12 cases for H. The sensitivity of Widal test for a titer 1/320 was 83.3% for O titer and 66.7% for H titer while the specificity was 61.7% for both O & H titer. We concluded from these study that there are high false positive rates of Widal test in normal population and in non typhoid fever , and Widal reaction in a titer 1/320 was found in many cases, and for these reasons the Widal test in the area endemic for typhoid fever provides minimal if any , diagnostic assistance, and a titer above 1/320 is suggested as a diagnostic value for salmonellae typhi infection .